The effectiveness of pancreatic enzyme replacement therapy for malabsorption in advanced pancreatic cancer, a pilot study. (February 2019) - Landers, Amanda; Brown, Helen; Strother, Matthew
Advanced adenocarcinoma of the pancreas has a globally poor prognosis. One of the characteristic features of pancreatic cancer (PC) is pancreatic exocrine insufficiency (PEI). This leads to a malabsorption syndrome and subsequent digestive symptoms. Given the high prevalence of PEI and malabsorption in PC, empiric use of pancreatic enzyme replacement therapy (PERT) is recommended. The aim of this pilot study was to determine the potential efficacy of PERT in improving symptoms and quality of life in those with metastatic PC. The study recruited patients with advanced PC referred to a specialist palliative care service. Following an initial assessment, patients were commenced on pancrealipase 25, 000IU (Creon) and reassessed after 1 week and 3 weeks post-initiation of supplementation. These assessments included demographics, malabsorption symptom checklist, and completion of two validated quality-of-life questionnaires, the European Organisation for Research and Treatment of Cancer QLQ-C30 and QLQ-PAN26. PERT was associated with statistically significant improvement of symptoms in both the general (QLQ-C30) and pancreatic cancer specific tool (PAN26). Within 1 week of PERT initiation, there was a reduction in diarrhoea scores (26 vs. 8, p <0.005), pancreatic and hepatic pain (47 vs. 33 and 24 vs. 11, respectively, p <0.05). After 3 weeks, there were significant improvements in pancreatic pain and bloating/gas symptoms (47 vs. 26 and 46 vs. 26, respectively, p < 0.005). PERT appears to have the potential to improve symptoms of malabsorption in patients with metastatic PC.